International Expansion Plan for Gentleman Store s.r.o. Company - Moravčík, Jan; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The thesis aims to determine whether an expansion to other European markets is a profitable choice for a Czech start-up company Gentleman Store, suggests the most suitable countries for expansion, entry mode and briefly shows steps that are to be taken in order to make the expansion successful. To reach the goal of the thesis, an extensive desk research was conducted to narrow down the choice of countries suitable for expansion. Then a qualitative research was conducted - for the 3 most relevant countries, a manager from a Czech company that has successfully expanded in that country was interviewed to see what is the best way of being profitable as a business in the given market. In the end, a feasibility study with a timeline, brief financial and risk assessment for the 3 most relevant countries was suggested.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses